Investigation of upper oligotrophic mires in the middle Ob basin (West Siberia); International Journal of Environmental Studies; Vol. 72, iss. 3 : The great Ob River basin - Rybina T. A. Tatjyana; Bazanov V. A. Vladimir; Savichev O. G. Oleg Gennadievich; Skugarev A. A. Andrei; Berezin A. E. Alexander; Sechenov V. A. Vyacheslav (2015, 2015)
Title screen